Development of entropy technologies for analysis and optimization of energy efficiency of technological systems - Samiilenko, Sergii; Hryshchenko, Roman; Kryvosheiev, Maksym (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is the energy efficiency of technological systems and complexes of enterprises. The study solved the problem of scientifically based technologies for system analysis and optimization of energy efficiency of multi-purpose systems. It is proved that the traditional definition of energy efficiency fails to identify the fundamental causes of inefficiency and assess the energy efficiency potential of the system. The use of exergy technologies is effective for optimizing heat engines, but for heat technology systems it gives rise to methodological contradictions. The presented entropic technologies for analyzing and optimizing energy efficiency do not have the indicated disadvantages. By combining entropic characteristics with energy characteristics, the “principle of energy compensation of irreversibility” was formulated, which is the basis of the analysis methodology. The results of the applied analysis of sugar production, which has an energy generation system and an energy technological complex of complicated configuration, showed the effectiveness of this technology. It was determined that compensation only for the internal irreversibility of the processes of the energy generating system consumes about 55% of the primary energy resource, which can change the classical concept of energy efficiency measures. The results obtained were made possible by establishing the dependence between the irreversibility of processes, entropy and compensatory energy costs. This allowed to approach the idea of energy efficiency in a new way, prioritizing the qualitative characteristics of processes and focusing on the thermodynamic perfection of systems. The proposed entropic technologies can be the basis for the formation of a comprehensive energy optimization strategy that has both economic and environmental effects, contributing to compliance with international standards of sustainable development